PERENCANAAN LABA DENGAN ANALISIS COST VOLUME PROFIT PADA PERUSAHAAN SEKTOR KESEHATAN YANG TERDAFTAR DI BEI - Ridwan, Rizky (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
The aim of this study is to determine how the quality of financial statements and corporate governance affect investment inefficiency. Indonesian state-owned enterprises are the object of this study. Quantitative method is used in this study, with secondary data sourced from state-owned enterprises in the period 2018-2022. This research uses quantitative methodology, with investment inefficiency as the dependent variable and audit committee, board of commissioners, and quality of financial statements as independent factors. Data analysis conducted by researchers using binary logistic regression, where the dependent variable is a dummy categorized as 0 and 1, using the help of SPSS software version 25. Based on the partial test results, this study concluded that the significance value (0.690) is more than the probability of 0.05, indicating that there is no significant relationship between investment inefficiency and the quality of financial statements. Considering that the probability of 0.05 is more than the significance value of 0.010, it can be concluded that the audit committee has a considerable influence on investment inefficiency. In addition, the board of commissioners has a significant effect on investment inefficiency ( at 0.027).